Hemispheric Specialization for the Visual Control of Action Is Independent of Handedness - Gonzalez, Claudia L. R; Ganel, Tzvi; Goodale, Melvyn A (Journal of neurophysiology, 2006)
Canadian Institutes of Health Research Group on Action and Perception, Department of Psychology, University of Western Ontario, London, Canada Submitted 9 November 2005; accepted in final form 20 February 2006 The idea that visually guided action is independent of visual perception has been supported by neurological, neuropsychological, and behavioral studies. In healthy subjects, evidence for this distinction has come from psychophysical studies of the effects of visual illusions on perceptual judgments and object-directed grasping. This evidence is limited, however, by the fact that virtually all studies have involved right-handed subjects using their dominant hand, which is presumably controlled by the left hemisphere. There is tentative evidence from earlier neurological studies that the left hemisphere may in fact play a special role in the integration of visual and motor information during grasping. We designed two experiments to test this idea. The first experiment involved pictorial illusions, which are known to have robust effects on perceptual judgments but little influence on grasping. Right- and left-handed subjects reached out and grasped objects embedded in two different visual illusions with either their dominant or their nondominant hand. For both right- and left-handed subjects, precision grasping with the left hand, but not with the right, was affected by the illusions. In a follow-up experiment, we examined precision grasping in a more natural setting and showed that left-handed subjects use their nondominant (right) hand significantly more as compared with right-handed subjects. We conclude that visuomotor mechanisms encapsulated in the left hemisphere play a crucial role in the visual control of action and that this hemispheric specialization evolved independently of handedness. Address for reprint requests and other correspondence: C.L.R. Gonzalez, CIHR Group on Action and Perception, Department of Psychology, University of Western Ontario, London N6A 5C2, Canada (E-mail: cgonzal6atuwo.ca )